Investigation of the effect of winding clamping structure on frequency response signature of 11 kV distribution transformer - Murthy, Avinash Srikanta; Azis, Norhafiz; Al-Ameri, Salem; Mohd Yousof, Mohd Fairouz; Jasni, Jasronita; Talib, Mohd Aizam (MDPI, 2018)
This paper presents an investigation on the sensitivity of frequency response of a 500 kVA, 11/0.433 kV distribution transformer with and without the presence of a winding clamping structure. Frequency response analysis (FRA) measurements of multiple test configurations were carried out with and without the presence of a winding clamping structure. Statistical analyses based on Pearson’s correlation coefficient (PCC), Spearman’s correlation coefficient (SCC), Kendall’s correlation coefficient (KCC), cross-correlation coefficient (CCF), root mean square error (RMSE), absolute sum of logarithmic error (ASLE), hypothesis test (F-test) and relative factor (RF) were applied to determine the effect of the winding clamping structure. It was found that the removal of the winding clamping structure has an impact on the frequency response signature at the frequency less than 2 kHz during offline measurement. It was found that ASLE and F-test are suitable methods that can be used to indicate the variation of frequency response caused by clamping structure removal of the distribution transformer under study.